The Effect of Work Motivation Mediation on the Relationship Between Work Environment and Employee Performance - Feriandy, Feriandy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Enhancing worker productivity is a crucial objective for any kind of firm. Employee performance might benefit from a positive work environment. Studies that particularly focus on the function of work motivation as a mediator in the interaction between the work environment and employee performance are scarce, nevertheless. This study aims to examine the role that work motivation plays as a mediator in the link that exists between the work environment and employee performance. This study uses a quantitative research method with a cross-sectional research design. The data was collected through a questionnaire distributed to employees in company X. With the use of the SPSS software, the gathered data was subsequently examined using a regression test. The study's findings demonstrate that the relationship between employee performance and the work environment is mediated by job motivation. Furthermore, employee performance is positively and significantly impacted by the work environment. An setting that is conducive to work can boost employee motivation, which in turn can enhance performance.